2014
DOI: 10.1080/17461391.2014.889757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12 weeks of dynamic strength training with local vibration

Abstract: The purpose of this study was to investigate the chronic effects of dynamic strength training (ST) with local vibration on the maximum strength of elbow flexor muscles. Twenty healthy male untrained volunteers were divided randomly into the following two groups: the conventional training group (CTG) or the vibration training group (VTG). Both groups performed ST for 12 weeks, three times a week. The ST protocol included four sets of 8-10 repetition maximums (RMs) of unilateral elbow flexion exercise. The VTG p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 34 publications
3
30
1
Order By: Relevance
“…In some investigations in literature 3,28 no effect or even a remarkable decrease of maximal force and strength related abilities is measured in the final test. Drummond et al 3 have shown that the application of local vibration does not change the chronic effects of dynamic ST in untrained individuals after 12 weeks. The main reason for this result often can be found in a too long and/or too intensive training schedule.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In some investigations in literature 3,28 no effect or even a remarkable decrease of maximal force and strength related abilities is measured in the final test. Drummond et al 3 have shown that the application of local vibration does not change the chronic effects of dynamic ST in untrained individuals after 12 weeks. The main reason for this result often can be found in a too long and/or too intensive training schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, target muscles can be stimulated more efficiently, resulting in the tonic vibration reflex (TVR) and, consequently, increasing the acute and chronic muscles' strength production. Many studies demonstrated significant chronic increases in the muscular force when conventional ST is combined with the use of mechanical vibration, and these increases can be acute or chronic [1][2][3] . The responses to both types of vibration training (WBV and LV) may lead to increased motor unit recruitment, increased firing frequency and/or improved synchronisation, thereby permitting a quicker and more forceful muscle contraction when the muscle is rapidly stretched.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This response to vibration resulting in the activation of an afferent feedback mechanism is known as tonic vibration reflex (TVR) (Hagbarth et al, 1996;.The stimulus generated by the mechanical vibration causes a high level of stress on the musculoskeletal system (Abercromby et al, 2007;Roelants et al, 2006;Marin et al, 2009), and the level of stress determines the training load, which consists of frequency, amplitude, acceleration, and duration of vibration on the musculoskeletal system (Cardinale et al, 2008;Rittweger, 2010).However, some anatomical structures such as soft tissues, bones, and body fluids absorb some vibration load during WBV, and therefore, affect the amount of vibration load transmitted to the muscles . The amount of vibration load depends on the distance between vibration source and target muscles and therefore the distal muscles may not effectively benefit from the vibration load to enhance performance (Drummond et al, 2014). However, local vibration (LV) may be more useful than WBV for targeting the muscles, because the muscles are directly exposed to the vibration in LV and absorption of the vibration is minimized (Drummond et al, 2014;Peer et al, 2009;Kurt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%